Impact of COVID-19 Lockdown on the Weaving Community of Western Odisha: A Study - Mishra, Shruti Sudha; Mohapatra, A.K. Das; Bhoi, Bhawanish (International Journal of Psychosocial Rehabilitation, 2020)
The crisis caused by COVID-19 has resulted in a sudden disruption of businesses across the globe, with India not being an exception. All economic activities in Odisha have come to a standstill owing to the lock down necessitated by the COVID19 pandemic. The handloom sector too got severely affected owing to a total closure of the traditional and contemporary markets for artisans. The weavers mostly from rural and remote areas have lost their livelihood, owing to large scale cancellation of orders and/or orders being put on hold. The weavers, considered as skilled worker in the segment, who live on the earnings of everyday work, are now sitting at home, next to their tools without any work in hand. The present study takes a dig into the economic conditions of the weaving community in the context of COVID 19 lockdown. It also endeavours to assess the impact of lock down on the livelihood of the weaving community belonging to selected districts in the Western part of the Odisha State in India.